(untitled) (Scientific journal of the Fergana State University, 2024)
This article will tell about the samples taken as an experiment. Today, there are several types of dried fruits and vegetables, and the quality of dried products varies. The drying method and all the samples obtained in this article are dried in an infrared drying device. The difference between samples obtained using this device and samples dried by other means is that the fruits are a microbiologist that is useful to the human body.